Alphabet (Kuala Lumpur Kohwai & Young Co, 2004)
This series of book has been specially designed to help the child learn letters, words and numbers easily. The child will also be able to develop early reading skills and a growing covabulary
Linguistic Notions
2
Keywords: Alphabet; English Language -- Alphabet; English Language